A Quantitative and Qualitative Assessment of Frozen Section Diagnosis Accuracy and Deferral Rate Across Organ Systems. Issue 6 (5th October 2022) - Mohamed, Anas; Hassan, Muhammad Masood; Zhong, Wen; Kousar, Aisha; Takeda, Kotaro; Donthi, Deepak; Rizvi, Areeba; Majeed, Marwan; Younes, Ahmed I; Ali, Ahlam; Sutton, Ann; Murray, Gina; et al.
Abstract: Objectives: Monitoring of frozen section diagnostic performance provides an important quality improvement measure. Methods: Surgical specimens involving a frozen section diagnosis over a 3-year period were retrospectively reviewed. Glass slides were reviewed on cases with discordance. Discordance and deferral rates were calculated. Results: Of 3, 675 frozen section diagnoses included, 96 (2.7%) were discordant with the final diagnosis. Additionally, 114 frozen section diagnoses (3.1%) were deferred. The organ-specific discordance rates were lowest in breast and genitourinary specimens and highest for pancreas, lymph node, and gynecologic specimens. Deferral rates were highest in musculoskeletal, breast, and hepatobiliary cases and lowest in thyroid, parathyroid, and neuropathology cases. Discordance was explained by block-sampling error (45%), specimen-sampling error (27%), or interpretation error (27%). Discordant frozen section diagnoses from gynecologic specimens were responsible for 81% of specimen-sampling errors; frozen section diagnoses of lymph nodes, head and neck, and pancreas were responsible for 54% of interpretation errors; 51% of block-sampling errors involved lymph node evaluation for metastatic carcinoma. Conclusions: Careful gross evaluation and microscopic examination of multiple levels should minimize specimen-sampling error and block-sampling error, respectively. Periodic review of accuracy and deferral rates may help reduce errors and improve the overall performance of this essential procedure.